Pengaruh Profitabilitas, Firm Size, Firm Growth, Likuiditas, Sales Growth Terhadap Nilai Perusahaan - Maurien, I Cenik Ardana (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to profitability, firm size, firm growth, liquidity, and sales growth towards firm value. Samples that have been selected by purposive sampling method and selected as many as 40 companies as a sample from 64 companies that go public listed on the IDX. The results of the research on profitability have significantly positive, firm size havenegative significant while the firm growth, liquidity, and sales growth have positive and not significant to the value of the company